Law Enforcement in the Aspects of Natural Resources and Environmental Damage - Prasetyo, Hery; Diniyanto, Ayon (Law Research Review Quarterly, 2021)
Development in humans and a country is a must. However, in development must apply a balance with nature and the environment. This is important because so far, development often has the potential to contribute to damage to natural resources and the environment. In Indonesia, there are several developments that provide evidence of damage to natural resources and the environment, even though Indonesia already has legal instruments to prevent and enforce violations of environmental damage. This phenomenon actually illustrates that the policies for protecting natural resources and the environment are still not optimal for the flow of development. This research examines the relevance between development and damage to natural resources and the environment. This research also analyzes law enforcement in the aspects of damage to natural resources and the environment.